Pelatihan Membuat Silase dari Tebon Jagung Sebagai Pakan Ternak di Kelompok Ternak Desa Wongkaditi Kecamatan Kota Utara Gorontalo - Umbang Arif Rokhayati (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2023)
The purpose of the dedication to making silage from corn stalks as animal feed in the Wongkaditi Village livestock group, Kota Utara Gorontalo district, is to increase knowledge and skills in utilizing waste from corn plants as livestock feed silage in the dry season. This service was carried out in March 2023 and took place in the village of Wongkaditi, Kota Utara District, Gorontalo. Another benefit that can be obtained from this service is that farmers can produce alternative feed without having to pay so much money in the summer, it can also generate economic value for the family by selling some of the silage that has been used as feed to other breeders. The method used in this service is the method of socialization and experimentation. The results achieved in this service activity can increase skills in using agricultural waste as animal feed, can increase the income of farmers from selling corn silage.